Novel kojic acid-polymer-based magnetic nanocomposites for medical applications - Hussein Al-Ali, Samer Hasan (Dove Medical Press, 2014)
Iron oxide magnetic nanoparticles (MNPs) were synthesized by the coprecipitation of iron salts in sodium hydroxide followed by coating separately with chitosan (CS) and polyethylene glycol (PEG) to form CS-MNPs and PEG-MNPs nanoparticles, respectively. They were then loaded with kojic acid (KA), a pharmacologically bioactive natural compound, to form KA-CS-MNPs and KA-PEG-MNPs nanocomposites, respectively. The MNPs and their nanocomposites were characterized using powder X-ray diffraction, Fourier transform infrared spectroscopy, thermogravimetric analysis, vibrating sample magnetometry, and scanning electron microscopy. The powder X-ray diffraction data suggest that all formulations consisted of highly crystalline, pure magnetite Fe3O4. The Fourier transform infrared spectroscopy and thermogravimetric analysis confirmed the presence of both polymers and KA in the nanocomposites. Magnetization curves showed that both nanocomposites (KA-CS-MNPs and KA-PEG-MNPs) were superparamagnetic with saturation magnetizations of 8.1 emu/g and 26.4 emu/g, respectively. The KA drug loading was estimated using ultraviolet-visible spectroscopy, which gave a loading of 12.2% and 8.3% for the KA-CS-MNPs and KA-PEG-MNPs nanocomposites, respectively. The release profile of the KA from the nanocomposites followed a pseudo second-order kinetic model. The agar diffusion test was performed to evaluate the antimicrobial activity for both KA-CS-MNPs and KA-PEG-MNPs nanocomposites against a number of microorganisms using two Gram-positive (methicillin-resistant Staphylococcus aureus and Bacillus subtilis) and one Gram-negative (Salmonella enterica) species, and showed some antibacterial activity, which could be enhanced in future studies by optimizing drug loading. This study provided evidence for the promise for the further investigation of the possible beneficial biological activities of KA and both KA-CS-MNPs and KA-PEG-MNPs nanocomposites in nanopharmaceutical applications.